Anti-Bribery Declaration (Study on Indonesian Construction Companies) - Elika Regni Utami; Paulus Theodorus Basuki Hadiprajitno (Owner : Riset dan Jurnal Akuntansi, 2025)
Bribery is the most serious type of corruption in Indonesia. Business can manage potential bribery practices by implementing Anti-Bribery Management System (ABMS). The ISO 37001 certificate is one part of ABMS and the government requires construction companies to have this certificate. Anti-bribery declaration shows that a company commitment to stakeholders to demonstrate transparency and comply with ethical standards. Implementing this strategy is effective in maximizing stakeholder trust. The objective of this study is to determine the influence of the board of directors on anti-bribery declaration. Characteristics of the board of directors include size, activities, gender diversity and expertise. Directors' activities is shown by how often they have meetings in a year. Gender diversity means having different genders represented, this happens when there are women on the board. Directors' abilities in the field of accounting or finance show their skills. This study was conducted on construction sector companies listed on the Indonesia Stock Exchange in 2020-2023 and obtained data from annual report on the Indonesia Stock Exchange and company website. The sample selection used in this quantitative research was purposive sampling and the results of this selection obtained 17 companies. The analysis techniques used logistic reggression analysis. The results of this study analysis are company’s anti-bribery declaration can be influenced by size, activities, and gender diversity. In contrast, director’s expertise inadequate influence on anti-bribery declaration.